2005
DOI: 10.1002/art.21470
|View full text |Cite
|
Sign up to set email alerts
|

Maintenance of exercise in women with fibromyalgia

Abstract: Objective. To identify predictors of maintenance of exercise for women with fibromyalgia (FM).Methods. Women with FM who had been randomized to the exercise arm of a clinical trial were studied prospectively during and 3 months following treatment. Subjects completed exercise logs weekly and returned the data via postal mail. Outcome variables were duration of aerobic and stretching exercises. Two separate multivariate models for longitudinal data were built with adjustment for in-treatment adherence and time.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
29
0
4

Year Published

2007
2007
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(35 citation statements)
references
References 42 publications
2
29
0
4
Order By: Relevance
“…Bush et al [15] found that the attrition rates for the AE intervention groups averaged 27% (SD 18.9%, range 0-67%). As shown by Dobkin et al [38], higher baseline disability and increases in barriers to exercise during treatment predicted worse maintenance of AE over follow-up period. Patients may beneWt from cognitive-behavior therapy (CBT) that could teach these patients stress management techniques to limit barriers to exercise participation.…”
Section: Discussionmentioning
confidence: 82%
“…Bush et al [15] found that the attrition rates for the AE intervention groups averaged 27% (SD 18.9%, range 0-67%). As shown by Dobkin et al [38], higher baseline disability and increases in barriers to exercise during treatment predicted worse maintenance of AE over follow-up period. Patients may beneWt from cognitive-behavior therapy (CBT) that could teach these patients stress management techniques to limit barriers to exercise participation.…”
Section: Discussionmentioning
confidence: 82%
“…From an economic perspective, walking is a health tool that is inexpensive, and if the patient maintains it, is efficient even when compared to pharmacological treatment, therefore reducing socio-sanitary public spending associated to fibromyalgia (Richards & Scott, 2002). Nevertheless, some studies have shown that patients tend to present poor adherence to different exercise recommendations, even walking (Dobkin, Abrahamovicz, Fitzcharles, Dritsa & Costa, 2005;Dobkin, Da Costa et al, 2006;Meyer & Lemley, 2000;Schachter et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…Da Costa et al [19] observed functional improvement and pain decrease in patients attending a home exercise program for 12 weeks. However, according to Dobkin et al [21], a supervised program results in additional benefits because of the lower long-term adherence observed in a home program. Tiidus et al [76], as well as Dawson et al [20], studied the benefits of physical training programs (including aerobic, strength and flexibility exercises).…”
Section: Therapy and Benefits Of Reconditioning Programsmentioning
confidence: 99%